Mapping Biology Knowledge - Fisher, K. author. aut Link
V, 217 p.
Keywords: Mapping Biology Knowledge addresses two key topics in the context of biology, promoting meaningful learning and knowledge mapping as a strategy for achieving this goal. Meaning-making and meaning-building are examined from multiple perspectives throughout the book. In many biology courses, students become so mired in detail that they fail to grasp the big picture. Various strategies are proposed for helping instructors focus on the big picture, using the `need to know' principle to decide the level of detail students must have in a given situation. The metacognitive tools described here serve as support systems for the mind, creating an arena in which learners can operate on ideas. They include concept maps, cluster maps, webs, semantic networks, and conceptual graphs. These tools, compared and contrasted in this book, are also useful for building and assessing students' content and cognitive skills. The expanding role of computers in mapping biology knowledge is also explored.